PENGEMBANGAN PENUNTUN PRAKTIKUM KOLOID BERBASIS INKUIRI TERBIMBING PADA SISWA DI KELAS XI IPA SMA NEGERI 1 SUNGAI RAYA - Tika Pratiwi; Dedeh Kurniasih; Rizmahardian Azhari Kurniawan (Jurnal Ilmiah Ar-Razi, 2018)
Colloid is chemistry material which can be teached by experiment method. However, teacher’s practical guide didn’t match with the students characteristics and laboratory equipment in SMA Negeri 1 Sungai Raya. Therefore, this research aimed to develope the colloid practical guide based on guide inquiry. This research method was used Borg and Gall’s development model. Sampling technique used in this research was purposive sampling technique. Samples are students at eleventh grade in IPA 1 and IPA 2 SMA Negeri 1 Sungai Raya. The data was collected by using questionnaires and posttest sheet. The results of the research showed that the colloid practical guide are valid, practice, and effective. Validity test consists of three aspects (content, media, and language) were obtained coefficient validity with the average 1.00 or can be categorized "very valid". The practicality test used questionnaires for teacher and students which obtained the average percentage is 91.6% or can be categorized "very practice". Meanwhile, the effectiveness test obtained the average of posttest is 94, with the completeness classical is 100% or can be categorized "very effective". Based on the results, the colloid practical guide based on guide inquiry can be used as learning materials for students at eleventh grade in the second semester of IPA SMA Negeri 1 Sungai Raya.Keywords: Based on Guide Inquiry, Colloid, Practical Guide, Research and Development